A kinetic study, thermal analysis and kinetic modeling on homo and copolymerization of 2-(N, N-diethylamino)ethyl methacrylate and PEGMA. (December 2018) - Quiñonez-Angulo, Priscila; Ruiz-Villegas, Jesús; Licea-Claveríe, Ángel; Ramirez-Jiménez, Alejandro; Miranda-Soto, Valentín; Zapata-González, Iván
Graphical abstract: Highlights: Estimation of the values of kp /kt 1/2 for the involved monomers. Estimation of reactivity ratios and nonideal random sequence of the copolymers. Modulation of the Tg values in the range −61 ≤  Tg  ≤ 20 °C, depending on the copolymer composition. Comparison of the experimental data and a basic kinetic model. Abstract: Copolymers containing 2-( N, N -diethylamino)ethyl methacrylate (DEAEMA) and poly(ethylene glycol) methyl ether methacrylate with Mn  = 500 g mol −1 (PEGMA500 ) are one of the most promising combinations of smart polymers with biocompatibility character for uses in medical applications. The homo and the copolymerization processes of these polymers have been studied via free radical polymerization in ethanol, resulting in first-order kinetics with respect to monomer in the homopolymerization for DEAEMA, and PEGMA500 when a high ratio initiator:monomer (≥1:100) is used. Additionally, the overall polymerization rate is ½ – order with respect to initiator concentration for DEAEMA, but it is not valid for the PEGMA500 polymerization. The value of kp /kt 1/2 is estimated to be 0.39 L 1/2  mol −1/2  s −1/2 for DEAEMA at 70 °C, while those values corresponding to PEGMA500 homopolymerization show a strong dependency of kt on the length of growing radicals. The estimated reactivity ratios ( rDEAEMA  = 0.81 ± 0.20 and rPEGMA500  = 0.73 ± 0.18 estimated by Tidwell and Mortimer method) predict the formation of copolymer with nonideal random sequence and an azeotropic composition. Thermal properties were also analyzed, the glass-transition temperature ( Tg ) values of poli(DEAEMA- co -PEGMA500 ) copolymers were measured and compared with Gibbs-Di Marzio equation. The experiments were well represented by a basic copolymerization model, considering the terminal model.